Taper Corrosion and Adverse Local Tissue Reactions in Patients with a Modular Knee Prosthesis. Issue 4 (18th December 2018) - Christiner, Tom; Pabbruwe, Moreica B.; Kop, Alan M.; Parry, Jeremy; Clark, Gavin; Collopy, Dermot
Abstract : Background: Corrosion has been documented in modular knee implants, but it has not been related to negative patient outcomes. We performed an observational retrieval investigation of 13 Stryker Triathlon TS modular knee implants, 3 of which were revised because of osteolysis and adverse local tissue reactions secondary to fretting corrosion at the modular junctions. Methods: Modular surfaces were examined for the presence and severity of corrosion, and factors that may influence the development of corrosion were investigated. Scanning electron microscopy and energy-dispersive x-ray spectroscopy were performed to evaluate implants with severe corrosion, and tissue samples were sent for histopathological analysis. Results: Mild to severe corrosion was present in association with 62% of modular tibial components and 75% of modular femoral components. Although tibial corrosion was less prevalent than femoral corrosion, it occurred earlier and with greater severity. Scanning electron microscopy and energy-dispersive x-ray spectroscopy demonstrated the appearances of fretting and corrosion of the modular junctions. Histopathological analysis of specimens from the 3 patients with adverse local tissue reactions demonstrated severe reactions to metal debris, including 1 reaction that was consistent with an aseptic lymphocyte-dominated vasculitis-associated lesion (ALVAL). Conclusions: To our knowledge, ALVAL and pseudotumors have not previously been reported secondary to corrosion of modular knee replacements. The threaded taper design and the release of cobalt-chromium ions and/or debris are implicated in the occurrence of the adverse local tissue reactions, osteolysis, and soft-tissue damage that we observed in our investigation. Clinicians should be aware of this possible complication associated with modular knee implants. Clinical Relevance: This article should raise clinician awareness of adverse local tissue reactions secondary to corrosion, potentially resulting in earlier recognition of this complication.